Making the most of the first prenatal visit: The challenge of expanding prenatal genetic testing options and limited clinical encounter time. (19th June 2020) - Farrell, Ruth M.; Pierce, Madelyn; Collart, Christina; Edmonds, Brownsyne Tucker; Chien, Edward; Coleridge, Marissa; Rose, Susannah L.; Perni, Uma; Frankel, Richard
Abstract: Objective: Advances in prenatal genetics place additional challenges as patients must receive information about a growing array of screening and testing options. This raises concerns about how to achieve a shared decision‐making process that prepares patients to make an informed decision about their choices about prenatal genetic screening and testing options, calling for a reconsideration of how healthcare providers approach the first prenatal visit. Methods: We conducted interviews with 40 pregnant women to identify components of decision‐making regarding prenatal genetic screens and tests at this visit. Analysis was approached using grounded theory. Results: Participants brought distinct notions of risk to the visit, including skewed perceptions of baseline risk for a fetal genetic condition and the implications of screening and testing. Participants were very concerned about financial considerations associated with these options, ranking out‐of‐pocket costs on par with medical considerations. Participants noted diverging priorities at the first visit from those of their healthcare provider, leading to barriers to shared decision‐making regarding screening and testing during this visit. Conclusion: Research is needed to determine how to restructure the initiation of prenatal care in a way that best positions patients to make informed decisions about prenatal genetic screens and tests.